Cullin 1 is not associated with late-onset preeclampsia (Universa Medicina, 2019)
BackgroundLate-onset preeclampsia (PE) is preeclampsia occurring after 34 weeks of gestational age or later.  Cullin 1 (CUL1), a proangiogenic protein, is expressed in the placenta, where an imbalance between proangiogenic and antiangiogenic proteins during gestation can cause disturbance of trophoblast invasion. This defect results in vascular ischemia that may produce preeclampsia. The objective of this study was to determine the correlation between CUL1 as proangiogenic factor and late-onset preeclampsia. MethodsThis study was of analytical observational cross-sectional design and involved 44 preeclampsia patients with ³34 weeks of gestational age (late-onset PE). The CUL1 level in the subjects’ sera, taken before they gave birth, and in homogenates of their placenta, obtained per vaginam or by cesarean section, were examined by the ELISA technique.  Statistical analysis was performed with the Spearman correlation test with significant p value of